Characteristics and outcomes among a hospitalized patient cohort with Streptococcus pneumoniae infection. Issue 18 (May 2020) - Micek, Scott T.; Simmons, James; Hampton, Nicholas; Kollef, Marin H.
Abstract : Abstract: Infection due to Streptococcus pneumoniae (SP) requiring hospitalization is common. However, recent clinical studies describing patient characteristics and outcomes for SP infection in adults requiring hospitalization are lacking. Our goal was to evaluate patient characteristics, contemporary antibiotic resistance, and clinical outcomes among hospitalized adults with SP infections. A retrospective cohort study was conducted at Barnes-Jewish Hospital (1350 beds) in St. Louis, Missouri, USA for years 2012 through 2016. During the study period, 358 hospitalized adults, excluding those with meningitis, were identified with SP infection. Forty-four patients (12.3%) died within 30 days of the identification of their infection. Among these infections, 99 (27.7%) were assessed to be hospital-acquired and 259 (72.3%) were community-onset infections. The majority of infections involved the respiratory tract (88.5%). Azithromycin resistance was the most common antibiotic resistance at 51.4%, followed by enteral penicillin resistance (45.3%), trimethoprim-sulfamethoxazole (34.1%), second-generation cephalosporin (cefuroxime) (30.7%), and meropenem (22.6%). There were 70 isolates (19.6%) classified as multidrug resistant. Independent predictors of hospital mortality included increasing weight in 1-kilogram increments (adjusted odds ratio [AOR], 1.02; 95% CI, 1.01 – 1.02; P  = .048), increasing Charlson Comorbidity Index scores (AOR, 1.31; 95% CI, 1.21 – 1.42; P  = .001), and the presence of septic shock (AOR, 3.89; 95% CI, 2.31 – 6.57; P  = .009). The median [interquartile range] hospital length of stay was 8.1 days [4.5 days, 16.8 days]. Hospitalized patients with infection attributed to SP have significant 30-day mortality and use of hospital resources. Antibiotic resistance is common among isolates associated with infection. Determinants of mortality are primarily severity of illness, underlying comorbidities and increasing patient weight. Efforts to improve the treatment and prevention of SP infections are needed.